169k views
1 vote
50 POINTS PLEASE HELP

50 POINTS PLEASE HELP-example-1

2 Answers

1 vote

Answer:

First simplify the numerator (x+3) (x-2) = x^2 -2x + 3x - 6 = x^2 + x-6

now factor the numerator (x+3) (x-2)

now find the restriction 3x-6=0 3x=6 x=2

now factor the denominator 3(x-2)

(x+3)(x-2)/3(x-2)

now cross off the (x-2)

and you are left with (x+3)/3

The restriction is X=2

The simplified fraction is (x+3)/3

User Tokosh
by
5.9k points
1 vote

first simplify the numerator (x+3)(x-2)=x^2-2x+3x-6=x^2+x-6

now factor the numerator (x+3)(x-2)

now find the restriction 3x-6=0 3x=6 x=2

now factor the denominator 3(x-2)

((x+3)(x-2))/3(x-2)

now cross off the (x-2)

and you are left with (x+3)/3

ANSWERS:

The restriction is X=2

The simplified fraction is (x+3)/3

User AllOutOfSalt
by
6.0k points